Risk factors for chronic kidney disease and septic shock with hypertension in adults and children - Javier, R. Mohamad; Salim, Jonathan; Aji, Bethari Lekso; Pradipta, Benardinus Prima Ardjie; Nur, Choirin; Muhammad, Iqbal; Aflah, Livaldi Naufal; Rettauli, Immaculata Agata Bornok; Audrey, Cristal; Wijayaningtyas, Irma; Kosen, Yosua Darmadi; Fajriyadi, Adhitya; et al. (Frontiers in Nephrology, 2025)
BackgroundChronic kidney disease (CKD) affects nearly 10% of the global population and often progresses silently to end-stage renal disease, requiring dialysis or transplantation. Hypertension, prevalent in both adults and children, is a key driver of CKD progression. Acute kidney injury (AKI), particularly sepsis-associated AKI (S-AKI), poses a critical risk for long-term renal dysfunction, especially in patients with pre-existing CKD. S-AKI, defined by abrupt renal function decline during sepsis or septic shock, can accelerate CKD progression, yet its risk factors and outcomes across pediatric and adult populations remain incompletely characterized.ObjectiveAims to systematically evaluate existing research on the relationship between Risk Factors for CKD and Septic Shock with Hypertension in Adults and Children.MethodsA systematic literature search was conducted using PubMed, Google Scholar, and the Cochrane Library for studies published between 2004 and 2024. Search terms included “chronic kidney disease,” “septic shock,” “hypertension,” and “acute kidney injury.” After applying PRISMA-based screening and eligibility criteria, 9 studies were included for qualitative synthesis.ResultsA total of 762 articles were identified through database searching. After screening and eligibility assessment, 9 studies were included in the final synthesis. The findings revealed that both CKD and hypertension are significant independent risk factors for S-AKI and septic shock. Preexisting albuminuria, uncontrolled blood pressure, advanced age, and diabetes mellitus were frequently associated with poor outcomes. Several studies highlighted the role of MPP and fluid resuscitation strategies in preventing AKI progression in septic patients. In pediatric populations, a history of AKI was strongly associated with new-onset hypertension and subsequent CKD development, increasing vulnerability to severe septic complications.ConclusionCKD and hypertension significantly increase the risk of septic complications and worsen renal outcomes, particularly in patients with fluid management challenges. Early identification of high-risk patients, individualized hemodynamic targets, and tailored fluid resuscitation strategies are critical in reducing morbidity and mortality. Special attention is needed in pediatric patients with limited nephron reserve, where long-term surveillance and early intervention may improve outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php, identifier PROSPERO (CRD420251146866).